Inovasi Pembelajaran Melalui Penelitian dan Pengembangan Bahan Ajar - Erlina, Erlina (Universitas Islam Negeri Raden Intan Lampung, 2016)
Learning innovation is a necessity that must be done in order to increase the quality of education. Learning innovation is needed in many aspects and factors of education, such as good facilities, curriculum, learning process, evaluation of education and improvement of teachers and the leraning participant quality. This article presents the idea of educational innovation in the development of teaching materials. There are three ways that can be used in developing teaching materials, namely: (1) writing itself (starting from scratch), (2) repackaging information, (3) structuring information (compilation). Teaching materials must meet the criteria: the accuracy of the content, the precision of coverage, the legibility of teaching materials, the use of language, packaging, illustrations, and completeness of the component. To produce teaching materials, need to be done through the stages of research and development, including: discover the potential and problems, data collection, product design, design validation, revision, product testing, product revision, utility testing, product revision, and mass production